Primary Cutaneous Follicle Centre Lymphoma with Hodgkin and Reed-Sternberg Like Cells: A Case Report and Review of the Literature - Fatima A. Aldarweesh; Diana O. Treaba (Case Reports in Hematology)
An elderly woman with a complex medical history presented with a left forearm mass that slowly developed for several months. The excisional biopsy of this skin mass was remarkable for involvement by a follicle centre cell derived lymphoma with a nodular and diffuse pattern associated with a subset of scattered Hodgkin and Reed-Sternberg like cells. Fluorescence in situ hybridization studies did not detect the presence of IgH-bcl2 fusion transcript, and molecular studies were negative for immunoglobulin heavy chain gene rearrangements and EBV DNA sequences. Hodgkin and Reed-Sternberg like cells are rarely reported in FLs, and the association with primary cutaneous follicle centre lymphoma is extremely rarely seen. To our knowledge, our case is the second case of primary cutaneous follicle centre lymphoma with Hodgkin and Reed-Sternberg like cells.